Determination of Glycerol in Biodiesel Using a Nickel(II) Oxyhydroxide Chemically Modified Electrode by Cyclic Voltammetry - Pott Marinho Ballottin, Daniela [UNESP]; Lataro Paim, Leonardo [UNESP]; Ramos Stradiotto, Nelson [UNESP] (Wiley, 2013)
A glassy carbon electrode chemically modified with nickel oxyhydroxide from a nickel hexacyanoferrate (NiHCF) film was used to determine glycerol in biodiesel by cyclic voltammetry. The modified electrode exhibited a linear response to glycerol concentration in the range from 0.05 to 0.35mmol L-1, and a detection limit of 0.030mmol L-1. The glycerol concentration found in the biodiesel sample was 0.156mmol L-1. The method developed in this study showed a recovery of (100.3±5.0)%. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Biodiesel; Cyclic voltammetry; Glycerol; Nickel oxy/hydroxide electrode